Impact of land tenure and other socioeconomic factors on mountain terrace maintenance in Yemen - Aw-Hassan, Aden; Alsanabani, Mohammed; Bamatraf, Abdul Rahman (International Food Policy Research Institute, 2000)
This paper describes the land property rights and tenure systems in the western escarpments of the Yemeni Highlands, and analyses the impact of land tenure arrangements and other socioeconomic factors on terrace maintenance. Owner-cultivated land is dominant in the terraced area, but more than one-third of the land is sharecropped. Terraces cultivated by landowners have a lower number of broken walls per hectare than those cultivated by tenants under sharecropping arrangements. This is more significant on sharecropped public (state and waqf) than private lands the reason being the lack of clearly defined responsibilities between tenants and landowners for maintenance and cost sharing. These responsibilities are defined in the customary rules of land use, but uneven power distribution, which favors landlords, results in lack of clear rules and enforcement mechanisms. The study recommends government action in strengthening existing local institutions in documenting sharecropping contracts, improving and targeting agricultural credit services, instituting better price policies, and improving technologies for farmers. These measures will likely increase land users’ expected returns to investment, particularly for food crops, and increase landowners’ willingness to invest in terrace maintenance.